Disparities of Health Infrastructure Development in Rural Areas of Murshidabad District, West Bengal, India: A Geographical Analysis - Md. Mustaquim; Hasib Hasan; Woheeul Islam (South India Journal of Social Sciences, 2024)
According to 2011 census, nearly 68.84% and 68.30% of total population resides in rural areas in India and West Bengal respectively. However, the infrastructure, resources, and production capacities of these villages vary, leading to distinct socio-economic groups based on their development levels. Such disparities pose challenges for a nation’s overall development. The present research paper emphasises the regional disparities in health infrastructure in Murshidabad district of West Bengal, and highlights healthcare facilities and challenges in the public health situation within the district. This study employs a comprehensive approach, utilising both secondary and primary data. Secondary data are collected from different sources and primary data are collected from a sample of 1,040 households distributed across the district. For data analysis, Z-score statistical method is applied, and for the preparation of maps, GIS technique is used. The findings of this research contribute to a nuanced understanding of health infrastructure challenges in the rural landscape of Murshidabad district. By delineating spatial patterns and identifying factors influencing its disparities, the study provides valuable insights for policymakers, healthcare practitioners, and community stakeholders. The outcomes are crucial for informing targeted interventions that promote equitable health infrastructure development in this diverse and geographically expansive district.